2021
DOI: 10.1016/j.dib.2020.106607
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on open/blind hole-hole interaction in barely visible impact damaged composite laminates

Abstract: This dataset contains the mechanical properties and structural characteristics with images of the carbon fibre reinforced epoxy composite (CFRP) laminates with open/blind holes. The mechanical dataset are the fracture strength, strain at fracture, strain energy density for resilience, strain energy density to fracture and stiffness of the CFRP laminates for different setups (namely 1 hole, 2 holes parallel to applied load, and 2 holes normal to applied load) from pristine and barely visible impact damage (BVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[ 21,37 ] Furthermore, there was no effect of hole–hole orientation (row of holes parallel/perpendicular to the applied load direction) and hole–hole separation distance (where the VHs were confined within the BVID region) on the mechanical properties. [ 20,22 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21,37 ] Furthermore, there was no effect of hole–hole orientation (row of holes parallel/perpendicular to the applied load direction) and hole–hole separation distance (where the VHs were confined within the BVID region) on the mechanical properties. [ 20,22 ]…”
Section: Resultsmentioning
confidence: 99%
“…(E) In-plane compression test. [13,[20][21][22] (F) Determining the mechanical properties from stress-strain curve obtained from compression testing. sonication (10 s) and rest (20 s), spanning 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, the fiber‐reinforced composite laminates were prone to impact damage when in service (i.e., aircraft taxing on the runway) and also damage that has been induced during maintenance 6,7 . The low‐energy impact damage on composite structure (i.e., carbon fiber reinforced thermoset polymer composite, CFRP) was barely visible to the naked eye but the structural integrity was compromised by about 50% reduction in compression strength 8–12 . To address this issues, several researchers reported that the epoxy resin (also referred to as adhesive) could be used to repair the impact‐type damage on the composite materials by using the resin‐injection method to restore the mechanical properties of the composite materials to its pristine conditions 13–17 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The low-energy impact damage on composite structure (i.e., carbon fiber reinforced thermoset polymer composite, CFRP) was barely visible to the naked eye but the structural integrity was compromised by about 50% reduction in compression strength. [8][9][10][11][12] To address this issues, several researchers reported that the epoxy resin (also referred to as adhesive) could be used to repair the impact-type damage on the composite materials by using the resin-injection method to restore the mechanical properties of the composite materials to its pristine conditions. [13][14][15][16][17] The literatures highlighted the key factors influencing the success of the resin-injection method, includes viscosity, 14,18 surface energy, 16 adhesion strength, 13 and mechanical properties 19 of the adhesive.…”
mentioning
confidence: 99%